Plan de desarrollo Y ordenamiento territorial (PDOT) de la parroquia Yangana, perteneciente al cantón Loja. - Espinosa Rodríguez, Carlos Augusto (2012)
This research work focuses the use of Geographic Information Systems (GIS) to the parish Zoning Yangana belongs to the canton Loja. With this perspective, carried out the assessment of the susceptibility, the Threat, Vulnerability and Risk based on a theoretical system, which is to assess quantitatively the most determining factors of the land which directly influence the appearance of new geological hazards. Is taken as a starting point topographic digital information sector with scale study to detail (1:50.000), based on this information and with the field work, we obtained thematic maps: geology, geomorphology, outstanding, current land use, urban land use, rainfall, vegetation and landslide inventory. Each variable is each of these thematic maps, has been valued based on the ability of each to be prone to landslides. With the help of Geographic Information Systems, processed in digital form each of the variables analyzed to overlay thematic maps and get the final map showing the areas of use in the study area. The information obtained in digital and analog form the basis for the parish Yangana, can perform the ordinances necessary because this information is described in areas where infrastructure may or may not make or developments, thus leading to improved conditions life of the people in charge and thus reach the Sustainable Development of the Parish Yangana, and look to achieve the proper management of resources both human and economic environment.